Is blue light exposure a cause of precocious puberty in male rats? - Uğurlu, Aylin Kılınç; Bideci, Aysun; Demirel, Ayşe Mürşide; Kaplanoğlu, Gülnur Take; Dayanır, Duygu; Gülbahar, Özlem; Bulut, Tuba Saadet Deveci; Döğer, Esra; Çamurdan, Mahmut Orhun (Frontiers in Endocrinology, 2023)
Purpose: Our study aimed to examine the effects of blue light exposure on prepubertal male rats’ puberty and testis tissue. Methods: Eighteen 21-day-old male Sprague Dawley rats were divided into three groups consisting of six rats in each group: Control Group (CG), Blue Light-6 hours (BL-6), and Blue Light-12 hours (BL-12). CG rats were maintained with 12/12-hour light-dark cycles. The rats of BL-6 and BL-12 were exposed to blue light (450-470nm/irradiance level 0.03uW/cm2) for 6 hours and 12 hours, respectively. Rats were exposed to blue light until the first signs of puberty. The ELISA method was used to analyze the serum levels of FSH, LH, testosterone, DHEA-S, leptin, ghrelin, melatonin, glutathione, glutathione peroxidase, and malondialdehyde. Testes were dissected for histomorphological examination. Results: The medians of the pubertal entry days of the CG, BL-6, and BL-12 were 38th, 30th, and 28th days, respectively. (p:0.001) The FSH, LH, and testosterone concentrations of all groups were similar. The FSH concentration increased as the LH concentration increased (r: 0.82 p: 0.001). The serum LH concentration increased as serum testosterone, and DHEAS decreased, respectively (r: -0.561, p: 0.01) (r:-0.55 p:0.01). Testicular lengths and weights of the BL groups were smaller compared to CG (p: 0.03),(p: 0.04). GPx was higher for BL-6 and BL-12 than the CG (p:0.021, p:0.024). Testis tissue was compatible with the pubertal period in all groups. As the blue light exposure time increased, spermatogenesis was suppressed, and capillary dilatation and edema in the testis tissue increased. Conclusion: Our study is the first to show the effects of blue light exposure on male rats’ puberty process. And we showed that exposure to blue light and the duration of exposure lead to precocious puberty in male rats. The blue light exposure suppressed spermatogenesis, marked vasodilatation in the interstitial area of the testis, and disrupted the integrity of the basement membrane. These findings intensified with increasing exposure time.